Interaction Between Chinese Medicine and Warfarin: Clinical and Research Update - Zhuang, Wei; Liu, Shaoli; Zhao, Xusheng; Sun, Nan; He, Tao; Wang, Yali; Jia, Beibei; Lin, Xiaolan; Chu, Yanqi; Xi, Shengyan (Frontiers in Pharmacology, 2021)
Warfarin is a commonly used oral anticoagulant. It has a narrow therapeutic window and wide variation in individualized dosing, and is used clinically for the treatment of thromboembolic diseases. Due to the widespread use of traditional Chinese medicine (TCM) in China and the complex composition and diverse mechanisms of action of TCM, the combination of TCM and warfarin in patients has led to fluctuations in the international normalized ratio of warfarin or bleeding. To ensure rational clinical use, we summarize the TCMs with which warfarin interacts and the possible mechanisms, with a view to providing a clinical reference. The mechanisms affecting the anticoagulant effect of warfarin are complex, and herbal medicines may enhance and diminish the anticoagulant effect of warfarin through a variety of mechanisms; thus, clinical use needs to be cautious. Some herbal medicines have shown inconsistent results in both in vivo and ex vivo experiments, pharmacology and clinical studies, and should be the focus of future research.